Evaluation of dum palm kernel activated carbon in chromium and lead adsorption from synthetic waste water - Mohammed, HI; Gutti, B; Highina, BK (International Journal of Environment, 2016)
This study aimed at the co-current removal of chromium and lead ions from synthetic waste water using dum palm kernel activated carbon. The adsorption experiment was conducted by varying time, pH and concentrations of the simulated solution. The data obtained were analyzed, and the best conditions for the uptake were at pH of 6, equilibrium time of 40 minutes. The two best isotherms models for the adsorption system were Sip, and Dubinin–Radushkevich, models respectively. Based on the Temkin adsorption energy calculated as 9.5793 and 0.4997 J/mol, the uptake of lead and chromium were chemisorption and physico-sorption, respectively. The maximum uptake calculated from Dubinin–Radushkevich plots were 14.1696 and 7.7191 mg/g, for lead and chromium, respectively. International Journal of Environment Vol.5(3) 2016, pp.104-118